On Security Issues in Modern Russia - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2022)
The scientific article discusses the concept and content of the security of the territory of the state, its varieties, as well as the importance of security for both the state and the individual and society. The author substantiates the need to single out such a variety of national security as food security.